Studying the changes in the characteristics of radiation-protective composition materials in dependence on homogeneity of distributing of metal components - Prokhorenko, E.M.; Lytvynenko, V.V.; Zakharchenko, A.A.; Khazhmuradov, M.A.; Prokhorenko, T.G. (Вопросы атомной науки и техники, 2019)
The dependence of the hardness of polystyrene-metal composite materials on the homogeneity of the distribution of particles of a component over the volume of a composite material is investigated. Improvements are made to thermoplastic-automata, which make it possible to improve the quality of composites production. The methods of IR-radiometric diagnostics of the component mixing efficiency are improved. The speeds of the mixer blades are experimentally determined depending on the size and number of particles of the metal components. Radiation protective characteristics were obtained for composite materials by numerical methods. Analyzed the attenuation of the absorbed dose of ionizing radiation, depending on the energy of gamma-rays. Досліджено залежність твердості полістирол-металевих композиційних матеріалів від однорідності розподілу часток компонент за об’ємом композиційного матеріалу. Запропоновано удосконалення термопластавтоматів, які дозволяють підвищити якість виготовлення композитів. Доопрацьовані методики ІЧ-радіометричної діагностики ефективності перемішування компонент. Дослідним шляхом визначено швидкості лопатей змішувача, в залежності від розмірів і кількості частинок металевих компонент. Для конкретних композиційних матеріалів чисельними методами отримані радіаційно-захисні властивості. Проаналізовано ослаблення поглиненої дози іонізуючого випромінювання в залежності від енергії гаммаквантів. Исследована зависимость твердости полистирол-металлических композиционных материалов от однородности распределения частиц компонент по объему композиционного материала. Предложены усовершенствования термопластавтоматов, которые позволяют повысить качество изготовления композитов. Доработаны методики ИК-радиометрической диагностики эффективности перемешивания компонент. Опытным путем определены скорости лопастей смесителя в зависимости от размеров и количества частиц металлических компонент. Для конкретных композиционных материалов численными методами получены радиационно-защитные характеристики. Проанализировано ослабление поглощенной дозы ионизирующего излучения в зависимости от энергии гамма-квантов.